Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Facile synthesis of β-functionalized “push-pull” Zn(II) porphyrins for DSSC applications - Prakash, K. (Dyes and Pigments, 2017)
Three new β-substituted “push-pull” Zn(II) porphyrin dyes with various electron donors at meso-positions and cyanoacetic acid as acceptor at β-position have been designed and synthesized. These porphyrins have been characterized by UV-Vis, Fluorescence, 1H NMR and 13C NMR spectroscopic techniques and cyclic voltammetric studies. The Soret and Q band of Zn(II) porphyrin dyes were found to be red-shifted (30–35 nm) as compared to ZnTPP. The fluorescence quenching and the decrement in quantum yield and lifetime suggest intramolecular charge transfer from donor to acceptor. Zn porphyrins exhibited anodic shift in their first redox potentials (0.03–0.11 V) as compared to ZnTPP. The HOMO-LUMO energy levels of Zn porphyrin dyes were compared with the conduction band of TiO2 and the electrolyte I−/I3 −. The HOMO levels of all the dyes are sufficiently higher than the energy level of electrolyte I−/I3 − and LUMO levels significantly lower than the conduction band of TiO2 which reflect the feasibility of facile electron-transfer. ZnT(Mes)P(CN-COOH) has been co-sensitized with N719 dye to further improve the PCE efficiency. These dyes displayed power conversion efficiency (PCE) of η = 1.72–3.13% where co-sensitized ZnT(Mes)P(CN-COOH) (N719) dye demonstrated maximum PCE efficiency up to 5.35%, with a Jsc of 11.8 mA cm−2, a Voc of 630 mV and a fill factor (FF) of 72% due to better light harvesting capacity.
Keywords: charge transfer; Conduction Bands; Cyanoacetic Acid; Electrolytes; Floorescence; Redox Reaction; zinc compounds